Anatomical parameters alter the biomechanical responses of adjacent segments following lumbar fusion surgery: Personalized poroelastic finite element modelling investigations - Nikkhoo, Mohammad; Chen, Wen-Chien; Lu, Meng-Ling; Fu, Chen-Ju; Niu, Chi-Chien; Lien, Hen-Yu; Cheng, Chih-Hsiu (Frontiers in Bioengineering and Biotechnology, 2023)
While the short-term post-operative outcome of lumbar fusion is satisfying for most of patients, the adjacent segment disease (ASD) could be prevalent in long-term clinical observations. It might be valuable to investigate if inherent geometrical differences among patients can significantly alter the biomechanics of adjacent levels post-surgery. This study utilized a validated geometrically personalized poroelastic FE modeling technique to evaluate the alteration of biomechanical response in adjacent segments post-fusion. Thirty patients were categorized for evaluation in this study in two distinct groups (i.e., (1) non-ASD and (2) ASD patients) based on other long-term clinical follow-up investigations. To evaluate the time-dependent responses of the models subjected to cyclic loading, a daily cyclic loading scenario was applied to the FE models. Different rotational movements in different planes were superimposed using 10N.m moment after daily loading to compare the rotational motions with the ones in the beginning of cyclic loading, as well. Biomechanical responses of the lumbosacral FE spine models in both groups were analyzed and compared before and after daily loading. The achieved comparative errors between FE results and clinical images were averagely below 20% and 25% for pre-op and post-op models, respectively, which confirms the applicability of this predictive algorithm for rough pre-planning estimations. The results showed that the disc height loss and fluid loss were increased for the adjacent discs in post-op models after 16h cyclic loading. In addition, significant differences in disc height loss and fluid loss were observed between the patients who were in non-ASD and ASD groups. Similarly, the increased stress and fiber strain in AF was higher in adjacent level of post-op models. However, the calculated stress and fiber strain values were significantly higher for the patient with ASD conditions. Evaluating the biomechanical response of pre-op and post-op modeling in the non-ASD and ASD groups showed that the inherent geometric differences among patients cause significant variations in the estimated mechanical response. In conclusion, the results of the current study highlighted the effect of geometrical parameters (which may refer to the anatomical conditions or the induced modifications regarding surgical techniques) on time-dependent response of lumbar spine biomechanics.